2020
DOI: 10.1080/23311886.2020.1774140
|View full text |Cite
|
Sign up to set email alerts
|

Youth health, gender, and social media: Mauritius as a glocal place

Abstract: The aim of this study was to investigate associations between social media use, self-reported health, dietary behaviours, and gender among young people living in Mauritius. For this cross-sectional study, questionnaires were distributed to a sample of 492 individuals (of which 64% were females) aged 14-29 year. A linear regression analysis investigating the associations between health problems and social media use, a number of dietary choices and behaviours, and gender was found to explain 49.9% of the varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…In addition, differences in the preferences of male and female participants were identified in this study, where female participants were more influenced by the use of social media for healthy diet management compared to males. These findings are similar to the studies conducted by Rambaree et al (20) and Boraita et al (21).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, differences in the preferences of male and female participants were identified in this study, where female participants were more influenced by the use of social media for healthy diet management compared to males. These findings are similar to the studies conducted by Rambaree et al (20) and Boraita et al (21).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was identified that young adults were more inclined toward the use of social media for their diet management, compared to older people (18). In relation to the gender, there is a significant difference between the genders in terms of social media use for dietary management (19,20). In a recent study, it was identified that females demonstrated higher vegetable consumption in the daily diet and greater satisfaction in the educational context compared to males (21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that social media has negative impacts on social life. For example, social media has an unfavorable impacts on the health of youth (Rambaree et al, 2020) and the social life of citizens (Mugari & Cheng, 2020). However, there are many positive impacts of social media on social life as contended by De Las Heras-Pedrosa et al (2020) that social media can be a promising health communication tool between hospitals and their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to the variable mentioned is described as follows. Research on social media has negatively impacted social life (Rambaree, Mousavi, Magnusson, & Willmer, 2020). Social media has a positive impact on financial efficiency (Parveen, Jaafar, & Ainin, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%